Factores de la teoría de Herzberg y el impacto de los incentivos en la satisfacción de los trabajadores - Madero Gómez, Sergio Manuel (Acta Universitaria, 2019)
Nowadays, companies need to develop and design attraction and retention strategies to help their employees be more productive and to find, through financial compensations, a stable source of income that meets their economic needs. This research work shows the preference and impact that the factors of the Herzberg’s theory have on job satisfaction. In this quantitative research, a questionnaire with 25 items was designed and applied to 423 people who work in Monterrey, Nuevo León, Mexico. It is highlighted that the recognition schemes (AV = 4.64 SD = 0.77) and the autonomy to make decisions (AV = 4.64 SD = 0.68) are the most important non-monetary aspects, whereas the Christmas bonus (AV = 4.69 SD = 0.62) is the most important from the monetary perspective.